The Gods Hate Fags: Falun Gong’s Reactionary Social Teachings - Zhang, Xinzhang (Journal of religion and violence, 2020)
In the ongoing struggle between Falun Gong and the Chinese state, Li Hongzhi’s reactionary social teachings are often mentioned in passing, but not examined in a systematic fashion. The present paper makes a preliminary effort in that direction, surveying Li’s homophobic, anti-miscegenist, anti-feminist et cetera pronouncements. On the one hand, these teachings often work at cross purposes with the movement’s efforts to garner support and to portray itself as the innocent victim of the Chinese state. On the other hand, the harshness of Li Hongzhi’s frequent pronouncements against gays, race-mixing and the like turn away potential supporters and provide critics with an abundant reservoir from which to fashion anti-Falun Gong discourse.